Disability and Vocational Rehabilitation in Rural Settings Challenges to Service Delivery (Springer International Publishing, 2018)
This first-of-its-kind textbook surveys rehabilitation and vocational programs aiding persons with disabilities in remote and developing areas in the U.S. and abroad. Contributors discuss longstanding challenges to these communities, most notably economic and environmental obstacles and ongoing barriers to service delivery, as well as their resilience and strengths. Intersections of health, social, structural, and access disparities are shown affecting rural disabled populations such as women, racial and sexual minorities, youth, and elders. In terms of responses, a comprehensive array of healthcare and health policy solutions and recommendations is critiqued with regard to health, employment, and service effectiveness outcomes. Included among the topics: Healthcare initiatives, strategies, and challenges for people with disabilities in rural, frontier, and territory settings. Challenges faced by veterans residing in rural communities. The Asia and Pacific region: rural-urban impact on disability. Challenges after natural disaster for rural residents with disabilities. Meeting the needs of rural adults with mental illness and dual diagnoses. Capacity building in rural communities through community-based collaborative partnerships. Disability and Vocational Rehabilitation in Rural Settings makes a worthy textbook for graduate students and upper-level undergraduates in the fields of social work, community and environmental psychology, public health, sociology, education, and geography. Its professional audience also includes vocational rehabilitation counselors serving these dynamic populations.